If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + -4 = 9(x + 7) Reorder the terms: -4 + 9x = 9(x + 7) Reorder the terms: -4 + 9x = 9(7 + x) -4 + 9x = (7 * 9 + x * 9) -4 + 9x = (63 + 9x) Add '-9x' to each side of the equation. -4 + 9x + -9x = 63 + 9x + -9x Combine like terms: 9x + -9x = 0 -4 + 0 = 63 + 9x + -9x -4 = 63 + 9x + -9x Combine like terms: 9x + -9x = 0 -4 = 63 + 0 -4 = 63 Solving -4 = 63 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 11+2y=6(y+1)+y | | (4x^3)+(3x^2)+2=0 | | 3x-7x+7=x-6+13 | | 7+(9+k)=84 | | X^3-3x^2-24x+17=0 | | 3(x-2)+5x=6x-8 | | 6x+x=42 | | 4(N-10)=6n+2 | | 4(N-10)=6 | | 11a+9*22=294 | | 11a+9c=294 | | 4(3x+2)(2x-7)= | | -u^2+9u+26=0 | | 10x+3=3(3x+7) | | x+-22-10y=-5 | | 11a+9c=780 | | .0002x+.05=.5 | | 1785=t-(836) | | a+5+4a=-5 | | 3+4(3a+7)=80 | | 27p^6m-343q^3n=0 | | 11a+14b=142 | | 2k+3(k+41)=-3 | | -3a-(-6a)+2a= | | 3x-9=2y | | (2a-3b)(5a^2-6ab+4b^2)= | | -0.3x^2+27x=0 | | -0.3x^2+27t=0 | | (x-16)+5=15 | | -127x=48 | | 2+5(3b+9)-9= | | 4(b+6)=6(b-36) |